SARS-CoV-2 Transmission Prevention Model Application in a Large Retail Company Before the Vaccine Introduction - Vitale, Ermanno; Vella, Francesca; Indelicato, Giuliano; Canalella, Andrea; Briguglio, Salvatore; Pittari, Veronica; Senia, Paola; Vinnikov, Denis; Floresta, Daniele; Rapisarda, Venerando; Filetti, Veronica (Frontiers in Public Health, 2022)
On 11 March 2020, following the spread of SARS-CoV-2, WHO declared a pandemic status. The impact on national health and economic systems has been huge. Therefore, many countries took measures to restrict the spread of the virus. Many work activities have been subjected to lockdown measures. However, some production activities, continued to remain open, i.e., large-scale food distribution, food industry, pharmacies, hospitals, etc. In order to contain the spread of the pandemic, public health measures have been implemented by the States to reduce the contagion of the virus in the workplace. Therefore, it was important to implement measures to contrast and contain the spread of SARS-CoV-2/COVID-19 in workplaces. The aim of this study was to adopt and implement a safety protocol useful to restrict the spread of SARS-CoV-2 in a large-scale retail trade company located in the south of Italy, before vaccination, during the first and second pandemic phases also exploiting telemedicine services. Antibody serological test cards were also used during the first pandemic wave and rapid antigenic swabs during the second to detect workers positive for SARS-CoV-2. A population of subjects who worked for another company similar for production activity and distribution on the territory was selected as the control group. During work activities, this group followed the minimum activity protocol provided by the Italian legislation (24 April 2020, Ministry Protocol), which provided the daily monitoring of the body temperature and in the case of SARS- CoV-2 positive subjects the extraordinary sanitation of the workplace. The measures implemented identified the positive subject for SARS-CoV-2 at an early stage. The protocol made it possible to significantly reduce the spread of the virus within large-scale retail distribution, and therefore, to avoid the temporary closure of the stores with a consequent reduction of economic losses compared with the control group.